PSYCHOLOGICAL AND PEDAGOGICAL ASPECTS OF DEVELOPING LOGICAL THINKING IN FUTURE EDUCATORS THROUGH INTERDISCIPLINARY COOPERATION (Scientific journal of the Fergana State University, 2023)
In this article, the pedagogical importance of developing logical thinking in future pedagogues through interdisciplinary cooperation, the pedagogical content of development, and the development of communication culture competence are an urgent task.